Cytomegalovirus Immunity After Alemtuzumab Induction in Desensitized Kidney Transplant Patients. Issue 7 (July 2017) - Ge, Shili; Karasyov, Artur; Sinha, Aditi; Petrosyan, Anna; Lovato, Darly; Thomas, David L.; Vo, Ashley; Jordan, Stan C.; Toyoda, Mieko
Abstract : Background: Desensitization with IVIG + rituximab combined with alemtuzumab induction gives HLA-sensitized patients an opportunity for successful kidney transplantation. However, it may be associated with a high risk for viral infections due to combined T cell and B cell depletion. Methods: Anti-cytomegalovirus (CMV) activity was assessed in 280 pretransplant and posttransplant blood samples from 33 desensitized patients who received alemtuzumab induction. CMV-specific CD8+ (CMV-Tc), CD4+ (CMV-Th) T cell activity, and natural killer (NK) cell number were measured by flow cytometry. Anti-CMV IgG was measured by enzyme-linked immunosorbent assay, and CMV DNA by polymerase chain reaction. Results: All 30 CMV sero (+) patients were (+) for CMV-Tc and/or Th predesensitization, while 3 sero (−) patients showed no CMV-T cell activity. CMV-Tc and/or Th became (−) in 50% to 70% of these sero (+) patients at 1 month post-alemtuzumab. However, 75% showed CMV-T cell (+) by 2 months and 95% did so by 3 months post-alemtuzumab. More than 50% of pretranslpant NK cell levels were detected post-alemtuzumab. Anti-CMV IgG levels did not decrease posttransplant in sero (+) patients. Four patients developed CMV viremia with clearance by 1.2 months, which correlated with an increase or appearance of CMV-T cells, even in the sero (−) patient. Conclusions: CMV-T cell activity, anti-CMV IgG, and NK cell-mediated antibody-dependent cell cytotoxicity were present in aleumtuzumab-treated CMV sero (+) patients. One sero (−) patient developed CMV-T cell responses post-CMV viremia. These results suggest that the IVIG + rituximab desensitization combined with alemtuzmab induction with triple immunosuppression maintenance does not result in prolonged suppression of anti-CMV immunity or increased risk for CMV infection. Abstract : Desensitization for HLA incompatibility using a combination of intravenous immunoglobulin G, rituximab and alemtuzumab induction with triple immunosuppression maintenance does not result in prolonged suppression of anti-CMV immunity or increased risk for CMV infection.